Children with Osteolytic Lesions - Enigmatic Presentation of a Life-Threatening Condition: Case Report and Literature Review - Lokesh Kumar; Himanshu Gupta; Siyaram Didel; Paras Tewari (The Korean Society of Pediatric Hematology-Oncology, 2024)
Pediatric acute leukemia presenting with osteolytic lesions and hypercalcemia is an unusual and rare occurrence. We are reporting two such cases with atypical presentations. The first case involved a 10-year-old boy who complained of progressively worsening lower back pain. Physical examination revealed restricted flexion and extension of the back due to pain, while complete blood count and peripheral blood smear were normal. CT and MRI spine indicated osteolytic lesions in all vertebrae and pelvic bones. Biopsies from the bone marrow and vertebrae confirmed the presence of lymphoblasts, with flow cytometry results positive for B-ALL. The second case involved a 2-year-old boy who presented with chronic fever, cough, and pain in the left hip region. Physical examination was unremarkable, but chest X-ray and CT thorax revealed mediastinal widening and an anterior mediastinal mass. Skeletal X-rays showed osteolytic lesions in the humerus and femur. Peripheral blood smear was suggestive of acute leukemia. Upon presentation, the child had a serum calcium level of 17 mg/dL, initially managed with fluids and furosemide, but also required zoledronate and calcitonin. Both these cases highlight that osteolytic lesions alone or combined with hypercalcemia can be the sole presentation of leukemia in children. Such cases require a high index of suspicion to diagnose this life-threatening condition promptly and initiate timely treatment for optimal outcomes.